Reshoring: implementation issues and research opportunities = Reshoring: aspekty zastosowań i możliwości badawcze - Ocicka, Barbara (Zielona Góra: Faculty of Economics and Management Press)
At the beginning of the 21st century, we continuously observe shifts in supply chains configurations caused by differentiate trends in turbulent environment. The remarkable number of companies restructure supply chains in search for competitiveness and innovation on global market.
Keywords: reshoring; produkcja; internacjonalizacja zakupów; zarządzanie łańcuchem dostaw; zarządzanie wartością; manufacturing; sourcing internationalization; supply chain management; value management